2013
DOI: 10.3171/2013.8.spine13183
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular pressure of the multifidus muscle and low-back pain after posterior lumbar interbody fusion: comparison of mini-open and conventional approaches

Abstract: Object. This randomized study was designed to elucidate the time course of the perioperative development of intramuscular multifidus muscle pressure after posterior lumbar interbody fusion (PLIF) and to investigate whether the route of pedicle screw insertion affects this pressure and resultant low-back pain. Although several studies have focused on intramuscular pressure associated with posterior lumbar surgery, those studies examined intramuscular pressure generated by the muscle retractors during surgery. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 27 publications
(19 reference statements)
1
31
0
Order By: Relevance
“…Previous reports have shown shorter hospitalization in patients undergoing MIS procedures, with decreases in LOS ranging from 15.0% to 64.0%. [30][31][32][33][34] Our results are consistent with these findings. We note that the percentage of procedures performed using MIS in this study is relatively low and lower than the national average, despite the study being performed at multiple centers.…”
Section: Discussionsupporting
confidence: 92%
“…Previous reports have shown shorter hospitalization in patients undergoing MIS procedures, with decreases in LOS ranging from 15.0% to 64.0%. [30][31][32][33][34] Our results are consistent with these findings. We note that the percentage of procedures performed using MIS in this study is relatively low and lower than the national average, despite the study being performed at multiple centers.…”
Section: Discussionsupporting
confidence: 92%
“…CBT surgeries usually involve a small skin incision. Back muscle retraction through this small skin incision increases the intramuscular pressure to a level that impedes local blood flow of the muscle and leads to muscle degeneration [ 19 , 20 ]. Postoperative magnetic resonance imaging demonstrated that the CBT screw head replaced the multifidus because of the screw’s medial-to-lateral orientation and caudo-cephalad pathway ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…They are located in the posterior vertebral spine and their function is the keep the torso upright while we are standing or sitting. [17][18][19][20][21][22] There is a close relationship between the paravertebral muscles and low back pain. Studies to evaluate the muscle strength of patients with mechanical low back pain have found severe hypotrophy of the paravertebral musculature of these patients among their results, showing the close relationship between mechanical low back pain and weakness of the paravertebrals.…”
Section: Low Back Painmentioning
confidence: 99%
“…The flexibility of the ischiotibial muscles is important for postural balance and to the maintenance of the total range of motion of the knee and hip. 19,20 Another very important factor is lack of physical activity, directly or indirectly related to back pain due to the shortening of muscles and overloads on the spine, making individuals more susceptible to low back pain. 3,[20][21][22][23][24] Sedentary individuals who had pain in the lumbar region and underwent a program of stretching followed by muscle strengthening experienced an improvement in body posture and a reduction in the incidence of lumbar pain at the end of treatment.…”
Section: Low Back Painmentioning
confidence: 99%